(untitled) (Biological Sciences - PJSIR, 2022)
Dry heat was more effective as physical mutagen than wet heat for Streptomyces rimosus. The optimal dose oftemperature for inducing auxotrophic mutants in Streptomyces rimosus was 55° under dry treatment conditions. Two mutants only out of 138 dry and wet heat mutants produced higher antibiotic titres than the parent organism.